The chinese version of the modification of diet in renal disease (MDRD) equation is a superior screening tool for chronic kidney disease among middle-aged taiwanese than the original MDRD and Cockcroft-Gault equations - See, Lai-Chu; Kuo, Chang-Fu; Yu, Kuang-Hui; Shen, Yu-Ming (Biomedical Journal, 2014)
Three equations have been often used to estimate glomerular filtration rate (GFR), namely, Modification of Diet in Renal Disease (MDRD), MDRD for Chinese (MDRDc), and Cockcroft-Gault (CG), for the purpose of screening individuals with chronic kidney disease (CKD). However, neither of these equations has been tested in a large Asian population. The aim of this study was to determine which equations were suitable for screening CKD in a large Taiwanese population. The applicability of the three equations was analyzed among 32,542 participants of a health examination at Chang Gung Memorial Hospital (CGMH), Taiwan, between 2005 and 2007. Estimated glomerular filtration rate (eGFR)-MDRDc obtained the highest estimate of GFR (mean 101.5 ± 19.2 ml/min/1.73 m 2 ), followed by eGFR-MDRD (mean 83.8 ± 15.8 ml/min/1.73 m 2 ) and eGFR-CG (mean 79.4 ± 29.1 ml/min/1.73 m 2 ). The prevalence of CKD stage 3-5 was 1.9%, 5.1%, and 25.5% according to MDRDc, MDRD and CG equations, respectively. With respect to CKD staging, the agreement between eGFR-MDRDc and eGFR-CG (weighted kappa, k = 0.22) and that between eGFR-MDRD and eGFR-CG (weighted k = 0.30) was poor. Both the original MDRDc and MDRD indicated that subjects with risk factors for CKD had significantly lower eGFR and higher odds ratios for stage 3-5 disease than those without. Paradoxically, the mean eGFR-CG (or odds ratios) was higher (or lower) in subjects with hyperuricemia, hypertension, obesity, or metabolic syndrome than those without these risk factors. The use of the CG equation in the Taiwanese population is inappropriate for screening individuals with CKD, and the MDRDc equation seems to be better for Taiwanese population.